1999
DOI: 10.1002/(sici)1521-396x(199911)176:1<231::aid-pssa231>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

MOVPE Growth and Luminescence Properties of GaAsN Alloys with Higher Nitrogen Concentrations

Abstract: Highly luminescent GaAsN alloy films have been successfully obtained with N concentrations up to 3.1% by metalorganic vapor phase epitaxy (MOVPE). The band-gap bowing parameter estimated from the photoluminescence (PL) peak energy is not constant but dependent on the N concentration; 24.0 eV for N < 1% and 17.0 eV for N > 1% at 20 K, and 22.4 eV for N < 1% and 14.5 eV for N > 1% at room temperature. From the characteristic features of the luminescence properties, the band-edge states are found to be much local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
14
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 14 publications
4
14
0
Order By: Relevance
“…Also, the samples examined here contained a relatively large amount of nitrogen (from 2% to 5%) and the bowing parameter could be different for smaller nitrogen contents [10]. However, the result is in good agreement with previous reports [8,11,12]. Fig.…”
Section: Resultssupporting
confidence: 90%
“…Also, the samples examined here contained a relatively large amount of nitrogen (from 2% to 5%) and the bowing parameter could be different for smaller nitrogen contents [10]. However, the result is in good agreement with previous reports [8,11,12]. Fig.…”
Section: Resultssupporting
confidence: 90%
“…The sources for Ga, As, and N were trimethylgallium, arsine, and 1,1-dimethylhydrazine, respectively. Owing to the optimization of the MOVPE growth, highly luminescent samples have been successfully obtained even without post annealing [4]. The PL measurements were carried out at 10 to 300 K using an Ar ion laser (488 nm, 10 mW) as the excitation source.…”
Section: Methodsmentioning
confidence: 99%
“…It is reported that the temperature dependence of the band gap energy of GaAsN alloy is smaller than GaAs from absorption measurements [2] and is explained in terms of band anticrossing model [3]. In addition, photoluminescence measurements revealed that the emission related to localized states results in the reduction of the PL peak energy shift due to the temperature change [4]. In this study we have measured photoluminescence (PL) spectra of GaAsN alloys to examine in detail the temperature dependence of the band gap energy and the influence of localized states.…”
Section: Introductionmentioning
confidence: 99%
“…Because the N incorporation generally introduces the high concentration free electrons, combined with the narrow-gap nature, the optical properties of InAsN near the bandgap are significantly affected by the Burstein-Moss (BM) effect (or band-filling effect) [1,3]. So, the bandgap narrowing with the N incorporation, which is commonly found in other III-V-N materials like GaAsN [5] and GaPN [6], is hardly observed in the bulk InAsN films. The band-filling effect is also expected in low-dimensional structures such as quantum wells (QWs).…”
Section: Introductionmentioning
confidence: 99%